Environmental Toxicity In Human Beings –A Solution Through Ayurveda - Godara, Sunita; Upadhyay, Parmanand; Sharma, Anita (International Research Journal of Ayurveda & Yoga, 2020)
Pollution is the introduction of contaminants into a natural environment that causes instability, disorder, harm and discomfort to the ecosystem. Due to the increase of day by day environmental pollution and slow chemical poisoning it may bring extinction of human race very soon. It has to be taken seriously, as it has a negative effect on natural elements that are an absolute need for life to exist on earth, such as water and air. Environmental pollution has five basic types of pollution, namely, air, water, soil, noise and light. Today not a single component of ecosystem remains free from pollution. It exerts harmful effects not only on human health but also destroys the environment which is the ultimately results in the destruction of life on planet earth. The need of herbs is increasing for human survival in the present day because the danger of slow chemical poisoning is ever present. Ayurveda meaning ‘the science of life’, explains that it is not only a science of medicine and medical cure of disease, symptoms only but it balances the total ecosystem of human life in the best way.